Gambaran Perkembangan Motorik Kasar Bayi Yang Diberikan Asi Non Eksklusif Di Desa Pesagi Kayen - Waty, Septy laras; , Sulastri, S.Kp., M.Kes (2017)
Background: Nutrition levels in the body play an important role for human survival. The development experienced by a toddler occurs gradually according to the flow of velopment. Toddler growth is also influenced by two factors, namely environmental factors and genetic factors. The biggest factor affecting the development of gross motor is infant acceptable nutrition especially exclusive breastfeeding, gross motor development is crucial for the development is crucial for development of overall baby skills. Objective: to know the picture of rough morotic developments of infants given non exclusive ation in the village of Pesagi Kayen. Method: This research type is descriptive analytic with approach method of cross sectional and total sample counted 51 sample. Results: Non-exclusive breastfed infants rienced a normal developmental stage of 19 infants (37.3%), caution categories of 18 infants (35.3%), and delay categories of 14 infants (27.5 %). Conclusion: The most dominant gross motor development in non-exclusive breastfed infants in Pesagi Kayen village is 15 children and there is a picture of rough motor development of infants who are given exclusive breast milk in the village of Pesagi Kayen.